2019
DOI: 10.47104/ebnrojs3.v1i3.67
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cancer Preventive Behavior among Nursing Males' Students: Intervention Guidelines

Abstract: Context: Testicular cancer is the most common form of urogenital cancers among young men aged between 20–40 years. The incidence of testicular cancer is rapidly increasing. It is highly curable when detected and treated early.   Aim: This study aimed to evaluate the effect of intervention guidelines on preventive behaviors among nursing males' students. Methods: A quasi-experimental study conducted at the technical institute of Beni-Suef university through the academic year (2018-2019). A convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
4
11
1
Order By: Relevance
“…Moreover, the concept of TSE as a screening procedure for early diagnosis of TC can be integrated into the undergraduate syllabus of all faculties. 34 In this study, while no significant differences (p > 0.05) were identified in the perceived susceptibility or importance/seriousness subdimensions of the CHBMS, significant differences (p < 0.05) were determined in the perceived benefits, barriers and self-efficacy/ confident sub-dimensions.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Moreover, the concept of TSE as a screening procedure for early diagnosis of TC can be integrated into the undergraduate syllabus of all faculties. 34 In this study, while no significant differences (p > 0.05) were identified in the perceived susceptibility or importance/seriousness subdimensions of the CHBMS, significant differences (p < 0.05) were determined in the perceived benefits, barriers and self-efficacy/ confident sub-dimensions.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, in a related study conducted with undergraduate nursing students, it was reported that previously percentage of informed related to testis cancer was 17.1% 33 . In other related studies carried out with students, too, it was revealed that over half of participants had no knowledge about TSE 15,22,34 . Similarly, in a study made with adult men, it was determined that 88.2% of them had not received training in the subject of TSE 35 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Concerning on Correlation between total knowledge of the male students' and their total practice at pre of an instructional supportive guideline, it indicated that the there was a highly positive association between total knowledge of male students and total practice at pre of an instructional supportive guideline. This finding is compatible with the prior study conducted by Ahmed et al, (2019) who performed study about "Testicular Cancer Preventive Behavior among Nursing Males' Students: Intervention Guidelines" and showed that there was a highly positive association between total knowledge of male students and total practice pre and post Intervention Guidelines. On other hand, this result disagreement with study by Mizie-Okoye et al, (2016) who conducted study about "Testicular Cancer Awareness and Testicular self-examination among senior secondary school students in Urban Local Government Area of Rivers State" and stated that there was a negative association between total knowledge of male students and total practice.…”
Section: Discussionsupporting
confidence: 91%